THE EFFECT OF GROWTH REGULATOR APPLICATION AND PLANTING MEDIA COMPOSITION ON THE GROWTH OF GARDENIA JASMINOIDES ELLIS SHOOT CUTTINGS - Hidayat, Hilmy Sayyidaffa Cahya; Hidayati, Nurul; Arfianto, Fahruddin (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2025)
Gardenia (Gardenia jasminoides Ellis) is an ornamental plant, with every part offering potential benefits. To obtain high-quality gardenia seedlings without altering the parent plant's characteristics, vegetative propagation through cuttings is employed. This study aimed to analyze and evaluate the effects of plant growth regulators (PGRs), growing media composition, and the combined influence of these two treatment factors. The research was conducted over four months at Jl. Yogyakarta No. 07, Menteng Urban Village, Jekan Raya District, Palangka Raya City, Central Kalimantan Province.This study utilized a factorial Completely Randomized Design (CRD) consisting of two factors with three replications. Treatment factor I involved five levels of plant growth regulators (PGRs), and treatment factor II consisted of three levels of growing media composition. The research results indicated that the single PGR treatment significantly affected shoot height at 40 and 60 days after planting (DAP), root count, shoot fresh weight, and cutting survival percentage. Conversely, the single treatment of growing media composition did not significantly affect any of the observed parameters. However, the interaction between the two treatments significantly influenced shoot height at 40 and 60 DAP, as well as root count. The 100 ppm IBA PGR treatment proved to be the most effective, yielding the highest shoot height (17.37 cm) and the highest root count (46.00).